Availability forecast of mining equipment. Issue 4 (10th October 2016) - Silva, Franco Jefferds dos Santos; Viana, Herbert Ricardo Garcia; Queiroz, André Nasser Aquino
Abstract : Purpose: The purpose of this paper is to present a methodology for forecasting the availability off-highway trucks used in a fleet for large transport operations of ore and sterile rock from an open pit mine. Design/methodology/approach: This methodology enables the estimation of the number of hours of preventive and corrective maintenance required, which are used to predict truck availability. The authors used historical data for the maintenance strategy based on the hours of operation. Findings: These data are statistically analyzed to obtain the key quantities and statistical models required to project availability and to develop equipment replacement plans. Originality/value: A methodology for forecasting availability to assets in open pit mining industry was implemented.